The urban life cycle and counter-urbanization dynamics in a north African context with: the case of Morocco - (:unkn) unknown (My University, 2022)
The urban life cycle theory suggests that urbanization occurs in phases according to the demographic evolution of the center of the Functional Urban Area (FUR) or its periphery. This paper aims to enrich the literature on urban life cycle theory by applying it to the context of a North African agglomeration: The Functional Urban Region (FUR) of Rabat, Morocco using demographic data from the period 1912-2014 (from the advent of the protectorate to the year of the last population census) as well as data on the mobility of the active population. The analysis reveals that Morocco experienced a phase of urbanization starting in 1912, suburbanization in the mid-1960s, and counter-urbanization starting in 1994. No signs of re-urbanization were found in the study area. The exploration of the phenomenon of counter-urbanization in light of mobility data highlights the different vocations of FUR’s small agglomerations as well as the differences in their degree of dependence on larger agglomerations, particularly Rabat.
Keywords: African Research